PENGARUH KOMPETENSI , DISPLIN KERJA TERHADAP KINERJA DIMEDIASI KOMITMEN ORGANISASIONAL (Pada SMP Negeri Di Kabupaten Pati) (Students' Journal of Economic and Management, 2012)
The purpose of this research was to examine the influence ofTeachers’ competence and Discipline toward Performance with Organizational commitment as mediation (Study at Secondary Schools Teachers in Pati Regency). The population in this research is all Junior High School Teachers of Civil Servants (PNS) in  Pati regency. Sample method applies Stratified Proportional Random Sampling using Slovin. The data are collected from 206 respondents by using sampling method.The instrument which is used in this research is computer software SPSS ver.16. program. Method of analyses to used linier regression analyses by conducting test of classic assumption and 5 hypothesis. The results of this research showed that the variables of Teacher Competency has a positive influence on Organizational Commitment, Discipline teachers have a positive effect on organizational commitment, competence of teachers has a positive influence on the performance of teachers, discipline has a positive impact on teacher performance, organizational commitment has a positive influence on the performance of teachers. And as a mediation, commitment organizational can’t be proved. It shows that commitment organizational can’t  mediate the influence of both competence and discipline toward teachers’ performance of junior high school teachers in Pati regency. Keywords: Teacher competence, discipline, Organizational Commitment, performance  teacher